Strange Reality: On Glitches and Uncanny Play - Holmes, Eben G. (Eludamos: Journal for Computer Game Culture, 2010)
Videogames have had to struggle with balancing the requirements of 'good' gameplay with a drive toward increasing graphical and narrative realism, spurred on by constantly improving technologies of simulation and computer graphics. Despite these advances in hardware and programming techniques, videogames' simulations of reality have, for the most part, remained crude and cartoonish next to the allegorical richness of description in art, literature and film-a comparison that may be unfair, but nevertheless has been relentlessly repeated. This paper attempts to highlight some of the difficulties and failures of realism in videogames through the lens of the uncanny, which, it is argued, should be understood as an essential trait of videogames in their capacity as simulations of realities, and as modern technology.